Hubungan Cryptocurrency dan Jumlah Uang Beredar di Indonesia Pasca Pandemi - Aulia Hassanah; Salsabila Sevira Putri; Sigit Aprizal; Cep Jandi Anwar (Peneliti.net, 2023)
This study aims to analyze the Relationship between Cryptocurrency and the Money Supply in Indonesia Post-Pandemic. The relationship between cryptocurrencies and the money supply is still evolving along with regulatory changes, mass adoption, and technological developments. Changes in the cryptocurrency ecosystem could have a significant impact on the financial system and the money supply in the future. This research is a quantitative research, the data is processed using Vector Error Correction Model (VECM) analysis. The results of this study show that in the short term the variables bitcoin, etherium and binance have no effect and are not significant at lag 1 real level 5%, while in the longterm variable bitcoin and binance have a significant effect on lag 1 real level 5%, setherium has no effect and is not significant at lag 1 real level 5%.